2006
DOI: 10.1002/jca.20082
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors that affect the mobilization of CD34+cells in healthy donors treated with recombinant granulocyte colony-stimulating factor (G-CSF)

Abstract: No specific characteristics have been identified as predictors of peripheral blood stem cells (PBSC) mobilization in healthy donors. In this study, clinical characteristics and laboratory data for 122 healthy donors who underwent apheresis on day 5 of treatment with recombinant granulocyte colony-stimulating factor (G-CSF) were retrospectively analyzed for correlations with CD34(+) cell mobilization. The variables that were analyzed included age, sex, body weight, basal complete blood count, and maximum white … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 31 publications
5
44
1
Order By: Relevance
“…Also in our study, as previously published in other case series, 9,19‐21 80% of donors reached the target dose for transplantation (CD34+≥4 × 10 6 /kg recipient in HLA‐full‐matched transplants). We registered only 4% (7/190) failures of PBSC collection (CD34+ <2.0 × 10 6 /kg recipient), requiring marrow harvest or a second donor mobilization, but we could not identify predictive variables others than the female sex and the premobilization CD34+, already mentioned.…”
Section: Discussionsupporting
confidence: 87%
“…Also in our study, as previously published in other case series, 9,19‐21 80% of donors reached the target dose for transplantation (CD34+≥4 × 10 6 /kg recipient in HLA‐full‐matched transplants). We registered only 4% (7/190) failures of PBSC collection (CD34+ <2.0 × 10 6 /kg recipient), requiring marrow harvest or a second donor mobilization, but we could not identify predictive variables others than the female sex and the premobilization CD34+, already mentioned.…”
Section: Discussionsupporting
confidence: 87%
“…Vasu and colleagues reported a reduced post–G‐CSF CD34+ cell count in females in their analysis of 639 allogeneic donors. Others found the same correlation …”
Section: Discussionsupporting
confidence: 58%
“…Restricting the recruitment to 'lighter' donors would carry an inherent conflict as several studies have shown that stem cell yields are positively correlated with donor weight. 83,84 The management of donors' expectations can similarly be important, especially in donors at increased risk of ARs. High-risk groups ought to be made aware of this at the time of their medical assessment.…”
Section: Possible Future Strategiesmentioning
confidence: 99%